Ambiguïtés, erreurs et conséquences : « Rendre l’œuvre lisible » - Michel Favre-Félix (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
According to majors codes of ethic, the aim of restoration is to « facilitate the reading » or « the understanding » of the objects. The notion of legibility applied to paintings is questioned (and opposed to the notion of perception). The idea that a work of art is created to deliver a “message” is criticized. These ambiguous terms appear to have misleading and falsifying effects on the restoration process and results.